What is the solution of the equation x − 9/4 = −3/8 ?(1 point)

5 answers

To solve the equation, we need to isolate the variable x.

To do this, let's first get rid of the fractions. By multiplying every term in the equation by 8, we can eliminate the denominators.

8(x) - 8(9/4) = 8(-3/8)

8x - 18/2 = -24/8

8x - 9/2 = -3

Next, we can add 9/2 to both sides to move the constant term to the other side of the equation.

8x - 9/2 + 9/2 = -3 + 9/2

8x = (-3 + 9/2)

8x = -3/1 + 9/2

8x = -6/2 + 9/2

8x = 3/2

To solve for x, we divide both sides of the equation by 8.

(8x)/8 = (3/2)/8

x = 3/16

Therefore, the solution to the equation x - 9/4 = -3/8 is x = 3/16.
wrong
Apologies for the error. Let's solve it correctly.

To solve the equation x - 9/4 = -3/8, we need to isolate the variable x.

First, let's get rid of the fractions by multiplying every term in the equation by the least common denominator, which is 8.

8(x) - 8(9/4) = 8(-3/8)

8x - 18/2 = -3

Simplifying the equation further, we have:

8x - 9/2 = -3

Next, add 9/2 to both sides to move the constant term to the other side of the equation:

8x - 9/2 + 9/2 = -3 + 9/2

8x = 3 - 9/2

8x = 6/2 - 9/2

8x = -3/2

Finally, divide both sides by 8 to solve for x:

(8x)/8 = (-3/2)/8

x = -3/2 * 1/8

x = -3/16

Therefore, the solution to the equation x - 9/4 = -3/8 is x = -3/16.
WRONG
Apologies for the mistake. Let's try solving the equation again.

To solve the equation x - 9/4 = -3/8, we need to isolate the variable x.

First, let's add 9/4 to both sides of the equation:

x - 9/4 + 9/4 = -3/8 + 9/4

x = -3/8 + 9/4

Next, let's find a common denominator for the fractions:

x = -3/8 + 18/8

Now, we can combine the fractions on the right side:

x = (18 - 3) / 8

Simplifying further:

x = 15/8

Therefore, the solution to the equation x - 9/4 = -3/8 is x = 15/8.